2016
DOI: 10.1136/bmjopen-2016-013167
|View full text |Cite
|
Sign up to set email alerts
|

Defining adolescent common mental disorders using electronic primary care data: a comparison with outcomes measured using the CIS-R

Abstract: ObjectiveTo compare the prevalence of common mental disorders (CMDs) derived from data held in primary care records with that measured using the revised Clinical Interview Schedule (CIS-R) in order to assess the potential robustness of findings based only on routinely collected data.Design and settingComparison study using linkage between the Avon Longitudinal Study of Parents and Children (ALSPAC) and electronic primary care records.ParticipantsWe studied 1562 adolescents who had completed the CIS-R in ALSPAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…CMD-case definitions in EHR include current codes relating to specific depressive and anxiety diagnoses, signs or symptoms [10]. Researchers can also choose to interrogate treatment codes or mental health referrals, codes for antidepressant or anxiolytic prescriptions or codes indicating an historical depressive or anxiety observation [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMD-case definitions in EHR include current codes relating to specific depressive and anxiety diagnoses, signs or symptoms [10]. Researchers can also choose to interrogate treatment codes or mental health referrals, codes for antidepressant or anxiolytic prescriptions or codes indicating an historical depressive or anxiety observation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There are some pitfalls to re-purposing primary care EHR data which may limit its effectiveness as a data source for mental health research. Poor EHR uniformity and maintenance can reduce reliability and primary care practitioners (PCP) rates of depression diagnosis are usually lower than rates examined in epidemiological studies [11], as they do not usually record codes with research purposes in mind [13]. Diagnostic coding can also differ significantly between clinicians and practices over time, making the identification of patients using a specific case definition more difficult [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed an increased risk of seeking primary health care for musculoskeletal pain in children/adolescents who had previously sought primary health care for sleep problems or psychological symptoms. While the size of estimates reported are modest in terms of the increase in risk to an individual, the evidence of the relatively high prevalence of sleep problems, psychological symptoms and musculoskeletal pain, within this population (Cornish et al, ; Henschke et al, ; Honaker & Meltzer, ; De Inocencio, ; Jordan et al, ; Meltzer, Johnson, Crosette, Ramos, & Mindell, ; Michaleff et al, ; van Suijlekom‐Smit et al, ) highlights the importance at a population level. Routine screening in primary care settings for the detection of children/adolescents with sleep problems and/or with psychological symptoms for early recognition of symptoms may be performed, and information and education given about potential risks as a pre‐emptive intervention (Kramer & Garralda, ; Meltzer et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Researching these associations in clinical settings would naturally exclude the mildest cases, as the pain is, by definition, important enough to seek health care for. While there is evidence that musculoskeletal pain, sleep problems, and psychological symptoms are common presentations in primary care for children/adolescents (Cornish, John, Boyd, Tilling, & Macleod, ; Henschke et al, ; Honaker & Meltzer, ; de Inocencio, , ; Jordan et al, ; Michaleff, Campbell, Protheroe, Rajani, & Dunn, ; van Suijlekom‐Smit et al, ), no studies to date have examined their relationships. The aim of this study was to investigate whether consultations for sleep problems or psychological symptoms are associated with subsequent consultations for musculoskeletal pain in children/adolescents in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…Depression and anxiety are among the leading causes of morbidity worldwide 1 , and typically first manifest during adolescence 2 . Longitudinal studies provide insight into the development of such common disorders [3][4][5][6][7][8][9][10] . Identification of risk factors is of vital importance for developing preventative and early intervention strategies to mitigate future morbidity and promote well-being 11,12 .…”
Section: Introductionmentioning
confidence: 99%